2008
DOI: 10.1007/s12094-008-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of unresected gastric cancer after laparoscopic diagnosis of peritoneal carcinomatosis

Abstract: Laparoscopic staging of gastric cancer can help to avoid unnecessary laparotomies. In patients with peritoneal carcinomatosis diagnosed by laparoscopy, nonsurgical treatment has low morbidity and mortality and permits good symptom relief with no shortening of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…This method involves image co‐registration of both CT and PET scans to produce a single image that depicts the spatial distribution and also demonstrate anatomic accuracy in localizing the site of metabolic activity, hence providing more precise anatomic localization to functional imaging which is lacking in pure PET scans. Alternatively, a minimally invasive approach of diagnostic laparoscopy may be performed to provide direct visualization of the peritoneal cavity 19–21. This technique is useful in assessing patients in whom there is inadequate information or uncertainty in the extent of carcinomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…This method involves image co‐registration of both CT and PET scans to produce a single image that depicts the spatial distribution and also demonstrate anatomic accuracy in localizing the site of metabolic activity, hence providing more precise anatomic localization to functional imaging which is lacking in pure PET scans. Alternatively, a minimally invasive approach of diagnostic laparoscopy may be performed to provide direct visualization of the peritoneal cavity 19–21. This technique is useful in assessing patients in whom there is inadequate information or uncertainty in the extent of carcinomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Early gastric cancers (T1 and T2) were included in ten studies [14, 16-18, 20, 21, 23, 24, 26, 30]. The tumor stage was not defined in seven studies [10,12,13,22,25,27,29]; however, all cases included were considered curative based on preoperative imaging.…”
Section: Tumor Stagementioning
confidence: 99%
“…Kaiser et al . (11-13) also reported similar metastasis detection rates for resectable M0 gastric cancer patients (20.6%, 24.7% and 23.0%, respectively). It is widely accepted that peritoneal dissemination spreads from the tumor to the serosa, but in our 51 DL+ patients, we also found 2 cT2N0 patients who had free cancer cells, 3 cT3N0 patients who had free cancer cells and 2 cT3N0 patients who had visible peritoneal dissemination.…”
Section: Discussionmentioning
confidence: 60%
“…(14) and Osorio et al . (13) reviewed patients who underwent diagnostic laparoscopy and laparotomy in the same period, respectively, and showed that there was no significant difference in the rate of intra-abdominal metastasis (45.2% vs . 35.5%, P=0.299; 20.6% vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation